2009
DOI: 10.1089/ten.tea.2008.0310
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus-Mediated Growth Factor Expression in Dedifferentiated Chondrocytes Accelerates Redifferentiation: Effects of Combinational Transduction

Abstract: Transduction of partially dedifferentiated rabbit chondrocytes with a baculovirus (Bac-CB) expressing bone morphogenetic protein-2 (BMP-2) reverses dedifferentiation and enhances matrix production. Hereby we examined whether transduction with Bac-CB in combination with another baculovirus expressing transforming growth factor-beta1 (TGF-beta1) or insulin-like growth factor-1 (IGF-1) synergistically augmented chondrogenic differentiation. Passage 3 rabbit articular chondrocytes were transduced by different bacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Culture in various types of three-dimensional scaffolds or hydrogels have been shown to re-differentiate de-differentiated chondrocytes (Capito and Spector 2006;Lin et al 2008;Malda et al 2003;Melero-Martin et al 2006;Stevens et al 2004;Takahashi et al 2007;Veilleux et al 2004). Growth factors, such as insulin-like growth factor-1, bone morphogenic protein-2 and TGF, also induce re-differentiation of de-differentiated chondrocytes (Liu et al 2007;Sung et al 2009). However, these methods require additional materials, which would increase the cost but hardly produce sufficient numbers of re-differentiated chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Culture in various types of three-dimensional scaffolds or hydrogels have been shown to re-differentiate de-differentiated chondrocytes (Capito and Spector 2006;Lin et al 2008;Malda et al 2003;Melero-Martin et al 2006;Stevens et al 2004;Takahashi et al 2007;Veilleux et al 2004). Growth factors, such as insulin-like growth factor-1, bone morphogenic protein-2 and TGF, also induce re-differentiation of de-differentiated chondrocytes (Liu et al 2007;Sung et al 2009). However, these methods require additional materials, which would increase the cost but hardly produce sufficient numbers of re-differentiated chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical analysis was performed between the same culture period secreted a higher level of TGF-b and exhibited a morphology of differentiated chondrocytes (Kessler and Grande 2008). TGF-b induces redifferentiated chondrocyte (Sung et al 2009;Liu et al 2007). In spinner culture of chondrocytes, the redifferentiation could be caused in part by enhanced TGF-b secretion, which was stimulated by shear stress.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have been followed by extensive work by Hu and co-workers, who have demonstrated the potential of baculovirus as a delivery vector for cartilage and bone tissue engineering (Lin et al, 2010b). The first indication of the possibility to use baculovirus vectors for cartilage engineering came from studies demonstrating efficient gene transfer into articular chondrocytes (Ho et al, 2004;Sung et al, 2007), which by combination of growth factor expression, such as bone morphogenetic protein-2 (BMP-2) and rotating-shaft bioreactor culture, allowed formation of hyaline cartilaginous tissues (Chen et al, , 2008Sung et al, 2009). When the chondrocyte cultures engineered this way were implanted into rabbits they were able to repair osteochondral defects at the patellar grooves .…”
Section: Ex Vivo Transductionmentioning
confidence: 99%
“…Lin et al 15 found that adenoviral vector-mediated BMP-4 had capability to recover chondrocytic phenotype of dedifferentiated chondrocytes in vitro and in vivo. A series of studies by Sung et al 23,24 demonstrated that transfer of BMP-2 or TGF-b1 via baculovirus could induce redifferentiation of dedifferentiated chondrocytes. Especially, the co-transduction of baculovirus-BMP-2 and baculovirus-TGF-b1 elevated the production of cartilaginous ECM molecules and maintained the chondrocytic phenotype.…”
Section: Discussionmentioning
confidence: 99%